TINJAUAN PELAKSANAAN PENGELOLAAN DOKUMEN REKAM MEDIS DI BAGIAN FILING DI PUSKESMAS WONOSARI 1 - Liss Dyah Dewi Arini; Ananda Meyrika Arthama; Darah Ifalahma (Universitas Duta Bangsa Surakarta, 2022)
Introduction: The implementation of the management of medical record documents at the Wonosari 1 Health Center there are still obstacles including in the medical record document storage section there is still a misfile because the medical record document after being used is not directly stored on the storage rack and there is still a buildup of medical record documents outside the medical record document storage rack and not yet there is a tracer. Objectives: The purpose of this study was to determine the implementation of medical record document management in the filing section at the Wonosari 1 Health Center.Methods: This research is a descriptive study with a cross sectional approach. The subjects of this research are filing officers and registration officers. The objects of this research are medical record documents, Standard Operating Procedures (SPO) and filing facilities. Result: The results showed that the implementation of storage and alignment of medical record documents was in accordance with Standard Operating Procedures (SPO), namely family folder storage and centralization, namely outpatient medical record documents, inpatient care, one family emergency room stored in one folder and the alignment based on Straight Numerical filing (SNF).Conclusion: the implementation of storage and alignment of medical record documents still found misfiles. this is because after used documents are not directly stored on the storage rack and the tracer aids are not used at the time of retrieval and return of medical record documents.